Treatment preferences among patients with mild-to-moderate atopic dermatitis - Kelley Myers; Jonathan I. Silverberg; Shreekant Parasuraman; Anna Pierce; Lawrence F. Eichenfield; Christine Poulos (Journal of Dermatological Treatment, 2023)
Study purpose: New treatments for atopic dermatitis (AD) are emerging; however, little is known about the treatment preferences of patients with mild-to-moderate AD. To measure patients’ preferences, a cross-sectional, web-based discrete choice experiment (DCE) survey was developed and administered to 300 adults in the United States with a self-reported physician diagnosis of mild-to-moderate AD. Materials and methods: In the DCE, respondents evaluated pairs of hypothetical AD treatment profiles defined by efficacy, risk, and mode and frequency of administration attributes. The DCE data were analyzed using a random parameters logit model. Subgroup analysis was used to investigate preference heterogeneity. Results: The results revealed achieving clear or almost clear skin within 3-4 months of treatment was the most important attribute relative to all other study attributes. The results indicated that a topical cream applied twice daily was preferred to systemic treatments. Subgroup analysis revealed that respondents with lower self-assessed disease burden were more likely to choose topical over systemic treatments and less averse to the risk of pain, burning, and/or stinging from the medicine (all other treatment features remaining equal) than respondents with higher self-assessed disease burden. Conclusion: The results of this study can help inform shared decision-making to manage mild-to-moderate AD.